2020
DOI: 10.1186/s10020-020-00247-2
|View full text |Cite
|
Sign up to set email alerts
|

Vagal afferent fibers contribute to the anti-inflammatory reactions by vagus nerve stimulation in concanavalin A model of hepatitis in rats

Abstract: Background Increasing number of studies provide evidence that the vagus nerve stimulation (VNS) dampens inflammation in peripheral visceral organs. However, the effects of afferent fibers of the vagus nerve (AFVN) on anti-inflammation have not been clearly defined. Here, we investigate whether AFVN are involved in VNS-mediated regulation of hepatic production of proinflammatory cytokines. Methods An animal model of hepatitis was generated by intrap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…In turn, the dorsal nucleus activates the efferent branch of VN to release acetylcholine, which binds to the α7 nicotinic acetylcholine receptor (α7nAchR) for its anti-inflammatory function [ 14 , 15 ]. α7nAchR, the most crucial molecule in CAP, can be activated and upregulated by VNS-induced endogenous acetylcholine [ 16 ]. Reportedly, α7nAchR-mediated CAP is closely related to many diseases in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the dorsal nucleus activates the efferent branch of VN to release acetylcholine, which binds to the α7 nicotinic acetylcholine receptor (α7nAchR) for its anti-inflammatory function [ 14 , 15 ]. α7nAchR, the most crucial molecule in CAP, can be activated and upregulated by VNS-induced endogenous acetylcholine [ 16 ]. Reportedly, α7nAchR-mediated CAP is closely related to many diseases in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…After the CS, rats were anesthetized with ketamine (80 mg/kg; Yuhan, Seoul, Korea) and xylazine (5 mg/kg; Bayer, Leverkusen, Germany). VNS in rats was given as described in our previous study [ 12 , 21 ]. Briefly, the anterior surface of the neck and the muscles were incised and the larynx was lifted.…”
Section: Methodsmentioning
confidence: 99%
“…Here, acetylcholine neurotransmitters released from the efferent fibers of the vagus nerve interact with ɑ7 nicotinic acetylcholine receptors (ɑ7 nAChR) in target cells (e.g., splenic macrophages) and subsequently induce the JAK2 activation of STAT3 and NF-kB leading to the inhibition of the expression of proinflammatory cytokine genes [ 8 , 9 ]. Since VNS is given to the exposed nerve in experimental animals, anti-inflammatory effects can also be influenced by afferent nerve activity through feedback loop in the dorsal vagal complex [ 10 12 ]. Moreover, VNS acting on the ascending fibers that transmit signals to the forebrain was reported to enhance memory formation and improve mental illnesses such as epilepsy and depression [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that JAK2-STAT3 pathway is involved in cholinergic anti-inflammatory effects through α7nAChRs after vagus nerve stimulation in macrophages 9 , 12 and liver cells 23 . However, STAT3 negatively regulates inflammatory responses primarily through anti-inflammatory effects of IL-10, an anti-inflammatory cytokine, without directly suppressing transcription of pro-inflammatory cytokines 24 .…”
Section: Introductionmentioning
confidence: 99%